Seismic retrofit of existing buildings : a guideline for practising engineers - Fox, Matthew; Kam, Weng Yuen; Grant, Damian (Emerald Publishing Limited, 2024)
Seismic Retrofit of Existing Buildings is a concise and easy-to-use book aimed at supporting engineers in the design of retrofit solutions for seismically vulnerable buildings. It offers readers guidance on both conceptual design strategies and relevant detailed design considerations, drawing from the authors' extensive experience in research and practice in seismic regions. Useful advice is provided on the design choices and detailing tips recognizing the practical implementation challenges behind these projects. It brings together the need-to-know information in one guide and will help you cut through conflicting advice, demystify technical jargon and interpret international standards to ensure that you have the right tools and knowledge in order to retrofit any building structure anywhere in the world. This book is unique in its coverage of a range of global and local seismic retrofit solutions applicable to buildings constructed in unreinforced masonry, reinforced concrete, structural steel and timber. Highlights include: background on seismic risk mitigation and the basis for retrofit; practical design tips and advice on consulting with clients; an overview of seismic assessment of existing structures, with reference to international standards including Eurocode 8, ASCE-41 and New Zealand standards; guidance on commonly used seismic retrofit solutions with supporting conceptual design examples; coverage of various construction types vulnerable to earthquakes and the specific retrofit techniques employed to improve their performance; commentary on future trends and the relevance of seismic retrofit of existing buildings to sustainability goals. It will be an indispensable companion for engineers, construction professionals and researchers, who seek to understand the principles behind seismic retrofit and the challenges and solutions in practical implementation.
Includes index.
Keywords: Earthquake resistant design.; Architecture / Security Design.; Building redevelopment, retrofitting, refurbishment.; Architectural structure and design.; Security and fire alarm systems.; elektronické knihy; electronic books